Bounded Rationality and Malaysian Housing Policy - Tan, Consilz; Entrekin, Leland; Butler, David (Thammasat Review of Economic and Social Policy, 2018)
The investment decision in real estate markets is becoming more challenging, due to rising property prices and the limited purchasing power of home buyers. There are numerous studies and statistics focused on property prices, mortgage eligibility, and lifestyle concepts. However, there is limited research on understanding the individual investors’ decision-making behaviour. This study aims to explore the investment decision in real estate markets by understanding both rational and boundedly rational behaviour of individual investors. We find that individual investors are affected by cognitive biases such as anchoring, endowment effect, loss aversion, and herding. Nonetheless, they are motivated by rational goals such as capital gain, long term investment, rental yield, and wealth accumulation. Our findings can assist Malaysian housing policy to achieve sustainability in the housing industry.